A study on management accounting practices in product cost measurement and the role of product cost information in pricing decision among SMIs / Ibrahim Morshidi - Morshidi, Ibrahim (2001)
This study contributes to the limited literature dealing with management accounting practices among small and medium industries in Malaysia (SMIs). Specifically, the study explores the accounting practices in the areas of product cost measurement and the role of cost information in pricing decision among SMIs in the Klang Valley. The extent of conventional management accounting techniques used in those areas as well as the trend in application of management accounting innovations is also investigated. The results of the study indicate that conventional management accounting practices are still prevalent in the areas of product cost measurements and pricing decisions. Even though innovations in the form of modern management accounting techniques are taking place in the SMIs, the overall impacts are not widespread. Collectively, the combined usages of multiple modern management accounting techniques are not likely to be applied by the SMIs.